Immune response against toxoplasmosis—some recent updates RH: Toxoplasma gondii immune response. (7th February 2022) - Sana, Madiha; Rashid, Muhammad; Rashid, Imran; Akbar, Haroon; Gomez-Marin, Jorge E; Dimier-Poisson, Isabelle
Aims: Cytokines, soluble mediators of immunity, are key factors of the innate and adaptive immune system. They are secreted from and interact with various types of immune cells to manipulate host body's immune cell physiology for a counter-attack on the foreign body. A study was designed to explore the mechanism of Toxoplasma gondii ( T. gondii ) resistance from host immune response. Methods and results: The published data on aspect of host (murine and human) immune response against T. gondii was taken from Google scholar and PubMed. Most relevant literature was included in this study. The basic mechanism of immune response starts from the interactions of antigens with host immune cells to trigger the production of cytokines (pro-inflammatory and anti-inflammatory) which then act by forming a cytokinome (network of cytokine). Their secretory equilibrium is essential for endowing resistance to the host against infectious diseases, particularly toxoplasmosis. A narrow balance lying between Th1, Th2, and Th17 cytokines (as demonstrated until now) is essential for the development of resistance against T. gondii as well as for the survival of host. Excessive production of pro-inflammatory cytokines leads to tissue damage resulting in the production of anti-inflammatory cytokines which enhances the proliferation of Toxoplasma . Stress and other infectious diseases (human immunodeficiency virus (HIV)) that weaken the host immunity particularly the cellular component, make the host susceptible to toxoplasmosis especially in pregnant women. Conclusion: The current review findings state that in vitro harvesting of IL12 from DCs, Np and MΦ upon exposure with T. gondii might be a source for therapeutic use in toxoplasmosis. Current review also suggests that therapeutic interventions leading to up-regulation/supplementation of SOCS-3, IL12, and IFNγ to the infected host could be a solution to sterile immunity against T. gondii infection. This would be of interest particularly in patients passing through immunosuppression owing to any reason like the ones receiving anti-cancer therapy, the ones undergoing immunosuppressive therapy for graft/transplantation, the ones suffering from immunodeficiency virus (HIV) or having AIDS. Another imortant suggestion is to launch the efforts for a vaccine based on GRA6Nt or other similar antigens of T. gondii as a probable tool to destroy tissue cysts.